Предмет: Алгебра,
автор: vitalina64
Упростить выражение , помогите у нас контрольная
Приложения:
Ответы
Автор ответа:
1
2а(5-3а)+(а-3)(а+7)=
= 10а - 6а² +а² + 7а - 3а - 21 =
= - (6а² - а²) + (10а + 7а - 3а) - 21 =
=- 5а² + 14а - 21
= 10а - 6а² +а² + 7а - 3а - 21 =
= - (6а² - а²) + (10а + 7а - 3а) - 21 =
=- 5а² + 14а - 21
Похожие вопросы
Предмет: Физика,
автор: dhsh15
Предмет: Математика,
автор: xx007xanger
Предмет: Химия,
автор: nikkostya323
Предмет: Химия,
автор: Nadia1999
Предмет: Математика,
автор: поли541